Frequency of renal dysfunction in cardiac surgery patients and its effect on outcome - K. Zakon; V. Romanova; K. Tverdohlib (Український Журнал Нефрології та Діалізу, 2018)
The purpose of this study was to define the frequency of renal dysfunction, including acute kidney injury (AKI), in cardiac surgery patients and its effect on outcome.